Aprendizagem de Gerentes em Organizações Não Governamentais no Nordeste Brasileiro - Silva, Lucimeiry Batista da (2009)
The main goal of this work is to comprehend the learning process of the managers in Non Governmental Organizations in the Northeast of Brazil. In order to achieve this proposal some specific goals have been established: a) identify the learning process of the managers in NGOS in the Northeast of Brazil; b) identify the role of the experience in the management learning process; c) identify the domains of learning of the managers in NGOS in the Northeast of Brazil and d) describe the meaning of being a manager in a NGO. The theory that has supported the investigation considered studies on the following themes: NGOS, to manage and guide, the theoretical segments of learning, the domains of learning and management learning. The methodological path that has been followed, had its starting point from an empirical research, through interviews with 16 managers of NGOS in the Northeast of Brazil. The research was guided by an interpretative paradigm and has used a qualitative approach, making use of discourse analysis as a tool to support the comprehensive interpretative analysis. As a result, it has been noticed that the learning process in NGOS in the Northeast of Brazil occurs in a dynamic and linked way integrated to the practice and, mainly, due to the demands of the managers´ jobs. Besides, there were found some specific domains during the process: the organizational domain (the learning about the organization), the instrumental domain (the learning about the work) and the individual domain (the learning about the self) and, based on the research a fourth one has appeared, the relational domain (the learning acquired from sharing the experience with the workmates and professional relations). Indicating how managers learn from their professional relationships. From various reports of the managers surveyed were able to identify the contribution of this area for learning managers in NGOs. The practical knowledge of management learning in NGOS has been influenced by the work environment, by the interaction through professional relations and by the self-knowledge. The research has concluded that the managers learn in the daily practice not only as a tool of acquisition of data, facts and practical knowledge, but also by the amount of knowledge from individuals and organizations. One can say that managers of NGOs learn about their work environment on three levels: the internal, about themselves, in their external actions, managers learn, for example, to deal with the funding agencies and international agencies to maintain institutional projects in operation. And the level of the social environment in which your organization operates, managers learn to overcome the barriers imposed by society, these barriers that often hinder the work of these managers. Finally, some implications and recommendations were presented to new researches with the aim to contribute to the development of studies involving the management learning and the learning in Non Governmental Organizations.